2016
DOI: 10.2147/ott.s104938
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapy for localized non-small-cell lung cancer: a review

Abstract: Targeted therapies have markedly improved the management of patients with advanced non-small-cell lung cancer (NSCLC), but their efficacy in localized NSCLC is less well established. The aim of this review is to analyze trials of targeted therapies in localized NSCLC. In patients with wild-type EGFR, tyrosine kinase inhibitors have shown no efficacy in Phase III trials. Few data are available for EGFR-mutated localized NSCLC, as routine biological profiling is not recommended. Available studies are small, ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Observational studies showed that recurrence might occur as early as 10 months after R0 resection, even with stage IA disease,20 indicating a poor prognosis 21. Nevertheless, R0 resection is curative for about 50% of patients with NSCLC, achieving long-term survival 22. Patients with the same stages of NSCLC or the same histological types may recur or not after complete resection 23.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies showed that recurrence might occur as early as 10 months after R0 resection, even with stage IA disease,20 indicating a poor prognosis 21. Nevertheless, R0 resection is curative for about 50% of patients with NSCLC, achieving long-term survival 22. Patients with the same stages of NSCLC or the same histological types may recur or not after complete resection 23.…”
Section: Discussionmentioning
confidence: 99%
“…So far, mutations of EGFR and translocations of the oncogenes encoding echinoderm microtubule-associated protein-like 4 ( EML4 ) -ALK had been identified as the most common ones [159] . Potent targeted agents against any of the identified specific genomic alterations would definitely improve the outcome of NSCLC cancer treatment [160] , [161] . Investigation of anti- ALK crizotinib (Xalkori), which targets EML4-ALK translocation, in patients with NSCLC showed promising results.…”
Section: Crizotinib Targeting Eml4-alkmentioning
confidence: 99%
“…It is a huge challenge for treatment, with a 5-year survival rate less than 18% 3, 4. Although there are multiple therapy strategies in treating lung cancer patients, such as surgery, chemotherapy, radiotherapy, molecular targeting treatment and immunotherapy 5-9, platinum-based chemotherapy is still the widely used first-line therapeutic regimen currently 10. However, the dose related toxicity and drug resistance are the main obstacles limiting the therapeutic efficiency of platinum-based chemotherapy, which are vary greatly among individuals 11, 12.…”
Section: Introductionmentioning
confidence: 99%